Study on the Impact of Agroforestry Intercropping Activities on Increasing Farmers' Income through the Social Forestry Program - Eryana Setyarti; Juliani Pudjowati; Elly Yuniar Nitawati (Journal of Economic Education and Entrepreneurship Studies, 2025)
Research in the KPH Malang reforestation park contract area aims to determine the level of dependence of farmers on forest resources and the role of Perum Perhutani in increasing farmers' income with the Agroforestry Tumpangsari system forestry program. This research requires empirical data that explains the effect of implementing intensification on productivity, income levels and efficiency of farmers participating in social forestry programs. The research results show that the influencing variables are capital, production results, and the number of program participants. Apart from that, there is a difference between the income of program participant farmers and non-program participant farmers. The government's efforts to conserve forests and carry out reforestation can be carried out well with cooperation between Perhutani and program participant farmers.